Techniques for analysing Late Cenozoic river terrace sequences - Stokes, Martin (2013)
This special edition presents a thematic set of eight papers examining field survey, remote sensing, and dating techniques used to analyse and interpret river terrace sequences. Most river systems from around the world have terrace landforms preserved at different altitudes along their valley sides. These landform sequences commonly span the Late Cenozoic encompassing hundreds of thousands to millions of years, providing an archive of long term fluvial landscape development and its driving mechanisms (Bridgland and Westaway, 2008a; Gibbard and Lewin, 2009; Westaway et al., 2009). River terrace sequences are an increasingly popular focus of earth science research (Vandenberghe et al., 2010). Whilst many collections of river terrace sequence research papers have primarily considered the environmental significance of such records (e.g. Vandenberghe and Maddy, 2000; 2001) less attention has been paid to the techniques used to collect the data. Thus, the purpose of this special issue is to bring together a set of research papers that demonstrate the multidisciplinary nature of river terrace sequence research. The special edition is also linked to two other research papers (Stokes et al., 2012; Veldkamp et al., 2012) that were incorrectly published as part of the normal research paper editions of Geomorphology. This editorial firstly provides an overview of river terrace sequence research providing definitions and explanations of key aspects of river terrace sequence formation. An overview of the key research groups that have been studying river terrace sequences in recent years is then provided. Finally, an introduction to the principal techniques used for river terrace sequence research is given, with brief overviews of the papers that form and are linked to this special issue.